Corrigendum: Multi-modal Brain MRI in Subjects with PD and iRBD - Mangia, Silvia; Svatkova, Alena; Mascali, Daniele; Nissi, Mikko J; Burton, Philip C; Bednarik, Petr; Auerbach, Edward J; Giove, Federico; Eberly, Lynn E; Howell, Michael J; Nestrasil, Igor; Tuite, Paul J; et al. (Frontiers in neuroscience, 2018)
[This corrects the article on p. 709 in vol. 11, PMID: 29311789.].
Keywords: functional connectivity; iRBD; Parkinson's disease; DTI; rotating frame MRI